Transformasi Digital: Pengembangan Sistem Informasi Penjualan Berbasis Web pada UMKM Barokah Jaya Cell di Bekasi dengan Pendekatan UI/UX - Farras Abiyyu Handoko; Tundo; Kastum; Fauzan Ibnu Sarky; Rohmat Wijaya (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study designs and develops a web-based sales information system for UMKM Barokah Jaya Cell in Bekasi using a UI/UX approach, applying the Waterfall method. The system development follows a structured process through requirement analysis, design, implementation, testing, and maintenance phases. The goal of this system is to improve efficiency in stock recording, sales transactions, and reporting. Evaluation was conducted through Time-on-Task Testing, Task Success Rate, Error Rate Analysis, and System Usability Scale (SUS). The test results indicate increased productivity, with faster task completion times, a task success rate improvement from 65% to 90%, and a reduction in errors in stock and transaction recording. With an average SUS score of 82, the system is considered intuitive, responsive, and easy to use.